Proyeksi Dampak Pertumbuhan Penduduk Provinsi Sumatera Utara di Tahun 2035: Analisis Geometri dan Eksponensial - Ramadhani, Rahmi; Siagian, Pargaulan (Sepren, 2024)
Population growth is an essential factor in community development in an area. The Sustainable Development Goals (SDGs) state that a country can achieve economic development and a significant demographic bonus by considering the rate of population growth. This study aims to analyze the results of projections related to the impact of population growth in the province of North Sumatra from 2020-2035 using geometric and exponential analysis approaches. This study uses geometric and exponential analysis, which has a good significance level and does not have a significant difference bias compared to other investigations. The research method used is qualitative research with a descriptive case study type. The data used is secondary data originating from the Central Statistics Agency of North Sumatra Province and the Ministry of Education and Culture. The data is analyzed using a geometric and exponential approach from 2021-2035. The results showed that the population growth rate of North Sumatra from 2020-2035 using both geometric and exponential analysis did not have a significant difference and had an increase. This study also found that the impact of population growth in North Sumatra has the potential for a sizeable demographic bonus by taking into account population density to equitable distribution of education. This study provides recommendations to policymakers to make policy improvements related to the rate of population growth in dealing with the ageing population and maximizing the demographic bonus obtained in 2035.